Venous thromboembolism: Past, present and future - Schulman, Sam; Ageno, Walter; Konstantinides, Stavros V. (Thrombosis and Haemostasis, 2017)
Venous thromboembolism (VTE), the third most frequent acute cardiovascular syndrome, is associated with a considerable disease burden which continues to grow along with the longer life expectancy of the population worldwide. In the past century, parenteral heparin prophylaxis was established for hospitalised patients at elevated risk of VTE. More recently, non-vitamin K antagonist oral anticoagulants (NOACs) with a direct inhibiting effect on factor Xa or thrombin, underwent extensive testing in clinical trials and have been approved for patients undergoing hip or knee replacement. Clinical investigation is ongoing in further areas of thromboprophylaxis, including medical prophylaxis in patients and high-risk situations in the outpatient setting. The diagnostic approach to suspected VTE is now based on advanced imaging techniques and robust diagnostic algorithms which ensure high sensitivity and specificity. Nevertheless, the role of clinical, or pre-test, probability assessment remains crucial to avoid overdiagnosis and treatment errors. Advances in reperfusion strategies, along progressive establishment of the NOACs as the new standard of anticoagulation treatment, have simplified the management of VTE, improving outcomes and particularly safety. While new molecular targets for anticoagulation are being investigated in the quest to further reduce bleeding risk, adjusting the initial regimen to the patient’s risk and finding the optimal duration of anticoagulation after an index VTE event will be some of the top priorities in the years to come. Importantly, and in parallel to new drugs and technical advances in imaging, incentives such as hospital accreditation and funding based on evidence-based practice need to be implemented to increase guideline adherence.
Keywords: Venous thromboembolism; deep-vein thrombosis; pulmonary embolism; prophylaxis; diagnosis; imaging; treatment; anticoagulants; reperfusion